Candidate Genes for Aggression and Antisocial Behavior: A Meta-analysis of Association Studies of the 5HTTLPR and MAOA-uVNTR - Ficks, Courtney A.; Waldman, Irwin D. (Behavior genetics, 2014)
Variation in central serotonin levels due to genetic mutations or experimental modifications has been associated with the manifestation of aggression in humans and animals. Many studies have examined whether common variants in serotonergic genes are implicated in aggressive or antisocial behaviors (ASB) in human samples. The two most commonly studied polymorphisms have been the serotonin transporter linked polymorphic region of the serotonin transporter gene ( 5HTTLPR ) and the 30 base pair variable number of tandem repeats of the monoamine oxidase A gene ( MAOA - uVNTR ). Despite the aforementioned theoretical justification for these polymorphisms, findings across studies have been mixed and are thus difficult to interpret. A meta-analysis of associations of the 5HTTLPR and MAOA - uVNTR with ASB was conducted to determine: (1) the overall magnitude of effects for each polymorphism, (2) the extent of heterogeneity in effect sizes across studies and the likelihood of publication bias, and (3) whether sample-level or study-level characteristics could explain observed heterogeneity across studies. Both the 5HTTLPR and the MAOA - uVNTR were significantly associated with ASB across studies. There was also significant and substantial heterogeneity in the effect sizes for both markers, but this heterogeneity was not explained by any sample-level or study-level characteristics examined. We did not find any evidence for publication bias across studies for the MAOA - uVNTR, but there was evidence for an oversampling of statistically significant effect sizes for the 5HTTLPR . These findings provide support for the modest role of common serotonergic variants in ASB. Implications regarding the role of serotonin in antisocial behavior and the conceptualization of antisocial and aggressive phenotypes are discussed.